Effect of Differences in the Composition of Growing Media on the Growth of White Oyster Mushroom Mycelium (Pleurotus ostreatus) - Elisa Herawati; Dwi Septi Amalia; Emi Malaysia; Agustina Murniyati; Fathiah (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
The use of the main growth medium in the form of wood sawdust in mushroom domestication is still higher than that of other organic materials, even though its availability is limited, so efforts need to be made to find a growth medium composition that minimizes the percentage of sawdust use. The purpose of this study was to determine the comparison of treatment 1 (80% teak sawdust, 10% bran, 5% tapioca flour, and 5% agricultural lime) with treatment 2 (70% teak sawdust, 15% bran, 10% tapioca flour, and 5% agricultural lime) on the percentage of growth and mycelium growth of white oyster mushrooms. Composting of growing media was carried out for 5 days, then baglog making was carried out, after which the baglog was sterilized for 4 hours. After sterilization, the baglog was cooled and inoculated. After inoculation, the baglog is incubated to grow mycelium. Then, after 15 days, data collection and calculation were carried out. The parameters measured were the percentage of growth and mycelium growth of white oyster mushrooms in baglogs. Results showed that the percentage of growth and mycelial growth of white oyster mushrooms in treatment 1 is better than in treatment 2. Reducing the percentage of the main growing medium of teak sawdust and adding the percentage of additional growing media of bran and tapioca flour has a negative impact on the number of baglogs that grow mycelium (percentage of growth) and the growth of white oyster mushroom mycelium. This means that reducing the main media of teak sawdust and adding additional media is not the right growing media composition for domestication of white oyster mushrooms, so it cannot be used as an alternative growing media composition to reduce the use of wood sawdust.